An O-Antigen Glycoconjugate Vaccine Produced Using Protein Glycan Coupling Technology Is Protective in an Inhalational Rat Model of Tularemia - Laura E. Marshall; Michelle Nelson; Carwyn H. Davies; Adam O. Whelan; Dominic C. Jenner; Madeleine G. Moule; Carmen Denman; Jon Cuccui; Timothy P. Atkins; Brendan W. Wren; Joann L. Prior (Journal of Immunology Research)
There is a requirement for an efficacious vaccine to protect people against infection from Francisella tularensis, the etiological agent of tularemia. The lipopolysaccharide (LPS) of F. tularensis is suboptimally protective against a parenteral lethal challenge in mice. To develop a more efficacious subunit vaccine, we have used a novel biosynthetic technique of protein glycan coupling technology (PGCT) that exploits bacterial N-linked glycosylation to recombinantly conjugate F. tularensis O-antigen glycans to the immunogenic carrier protein Pseudomonas aeruginosa exoprotein A (ExoA). Previously, we demonstrated that an ExoA glycoconjugate with two glycosylation sequons was capable of providing significant protection to mice against a challenge with a low-virulence strain of F. tularensis. Here, we have generated a more heavily glycosylated conjugate vaccine and evaluated its efficacy in a Fischer 344 rat model of tularemia. We demonstrate that this glycoconjugate vaccine protected rats against disease and the lethality of an inhalational challenge with F. tularensis Schu S4. Our data highlights the potential of this biosynthetic approach for the creation of next-generation tularemia subunit vaccines.